Comparison of hysteroscopic and laparoscopic myomectomy in large type 2 submucous leiomyomas - Taneja, Ashima; Kaur, Manpreet; Kaur, Amandeep; Arora, Mehak; Singh, Parampratap; Goyal, Mayur (International Journal of Research in Medical Sciences, 2023)
Background: Uterine leiomyomas are the most common benign tumors, affecting 30% of women of reproductive age. Submucous myomas are seen in 5.5-10% of all myomas. This study aimed to compare clinical, peri, and post-op outcomes of hysteroscopic and laparoscopic myomectomy in large type 2 submucous myomas. Methods: A prospective study was performed on 50 patients with large submucous type 2 leiomyomas measuring 3-5cm from October 2020 to August 2022. Patients were randomized into two groups of 25 each. Group A underwent hysteroscopic myomectomy and group B underwent laparoscopic myomectomy. Results: There was no significant difference in the demographic data of both groups except parity. Perioperative outcomes including bleeding, pain, and hospital stay were significantly higher in the laparoscopy group. None of our patients had air embolism. One patient had blindness in the postoperative period. 2 patients had uterine perforation in the hysteroscopy group. Postoperative pain was higher in the laparoscopy group. Recurrence at 3 months was seen in 2 patients of group A. Asherman syndrome was seen in group A. Single-stage success rate was seen higher in the laparoscopy group. Conclusions: Laparoscopy and hysteroscopy both are feasible techniques of myomectomy for submucous leiomyomas but for removal of large submucous leiomyomas laparoscopy myomectomy is considered better. For successful removal of large myomas in single-stage hysteroscopy, use of hysteroscopic morcellation should be considered.